Peran Penyuluh Agama Islam Dalam Memberikan Pencerahan Rohani Terhadap Masyarakat Di Kawasan Pinggiran Kecamatan Pahandut Kota Palangka Raya - Halimah, Halimah; Fatmah, Nor (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
This research focuses on the role of Islamic Religious Counselors in providing spiritual enlightenment to people in suburban areas using a qualitative approach and descriptive qualitative research type. Interview and documentation data collection techniques. The data source in this research was obtained from the main informant, namely the Islamic Religious Counselors at the Office of Religious Affairs (KUA). The research results show that the role of Islamic Religious Counselors is in providing spiritual enlightenment with material presented about religion, worship, morals and muamalah using the verbal da'wah method.